Causal factors for implementing environmental regulation: evidence from the erosion and sediment control plan in malaysia - Asri, S. Asnor; Rahimi, A. Rahman; Saffuan, Wan Ahmad (Penerbit Universiti Malaysia Pahang, 2020)
Erosion and sedimentation can have a significant impact on the environment. Therefore, the Erosion and Sediment Control Plan (ESCP) is necessary to reduce the adverse effects of those processes. Even though implementing ESCP is compulsory, we still have implementation issues in practice. This study aims to investigate the causal factors that are affecting ESCP implementation in Malaysia. To achieve that objective, data are collected through individual interviews with industry practitioners related to ESCP implementation. Then, the data are analyzed using the thematic analysis. The major findings are: (1) the challenges for ESCP implementation involve both internal and external challenges; and (2) the success factors for ESCP implementation relate to strategic focus, people, operations, and finances. This research contributes to the body of knowledge by providing insights into ESCP implementation, which could help develop policies and strategies to tackle the challenges. The findings of this research would help improve the success rate of ESCP implementation in Malaysia.